CREATION OF A SYSTEM FOR PREDICTING FAULTS IN SEWING EQUIPMENT BASED ON MACHINE LEARNING - Ibroximova Maftunaxon Nozimjon qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation. In the process of development of modern industry, ensuring the uninterrupted operation of production systems, increasing the reliability of equipment and reducing maintenance costs is becoming increasingly important. Especially in the light  industry,  in  particular  in  the  garment  industry,  since  each  element  of  the production line is closely interconnected, the failure of one piece of equipment can stop the entire production process. Therefore, the enrichment of technical service systems with innovative approaches is an urgent issue.